Analysis of Learning Implementation and Classroom Management at IRA Private Junior High School Medan: An Observation Study of PPL 1 - Siregar, Nuri Handayani; Wulandari, Windi; Rahmah, Mulia; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
This study aims to evaluate the implementation of education and classroom management at IRA Private Junior High School in Medan based on observations made during the first teaching practice (PPL I). The research method used is descriptive qualitative, with data collected through non-participatory observation, semi-structured interviews, and documentation of learning tools and activities that take place in the classroom. The findings of this study indicate that the implementation of learning is in accordance with the principles of the Merdeka Curriculum, which is characterized by the preparation of learning tools such as Annual Programs, Semester Programs, and teaching modules, as well as the use of interactive methods such as group discussions, presentations, and exercises based on Student Worksheets. Classroom management was also carried out well, as demonstrated by flexible seating arrangements, efficient time management, enforcement of classroom rules, and positive interactions between teachers and students. However, there were several challenges, such as limited use of digital media, short learning time, large number of students in one class, and inconsistent implementation of formative assessment. Overall, teaching practices and classroom management at IRA Private Junior High School in Medan are quite good and support the creation of an ideal learning environment, but there is still room for improvement in terms of learning differentiation, the use of interactive media, and strengthening the evaluation of the learning process.